Mutations of NOTCH3 in childhood pulmonary arterial hypertension. Issue 3 (1st April 2014) - Chida, Ayako; Shintani, Masaki; Matsushita, Yoshihisa; Sato, Hiroki; Eitoku, Takahiro; Nakayama, Tomotaka; Furutani, Yoshiyuki; Hayama, Emiko; Kawamura, Yoichi; Inai, Kei; Ohtsuki, Shinichi; Saji, Tsutomu; et al.
Abstract Mutations of BMPR2 and other TGF‐β superfamily genes have been reported in pulmonary arterial hypertension (PAH). However, 60–90% of idiopathic PAH cases have no mutations in these genes. Recently, the expression of NOTCH3 was shown to be increased in the pulmonary artery smooth muscle cells of PAH patients. We sought to investigate NOTCH3 and its target genes in PAH patients and clarify the role of NOTCH3 signaling. We screened for mutations in NOTCH3, HES1, and HES5 in 41 PAH patients who had no mutations in BMPR2, ALK1, endoglin, SMAD1/4/8, BMPR1B, or Caveolin‐1. Two novel missense mutations (c.2519 G>A p.G840E, c.2698 A>C p.T900P) in NOTCH3 were identified in two PAH patients. We performed functional analysis using stable cell lines expressing either wild‐type or mutant NOTCH3. The protein‐folding chaperone GRP78/BiP was colocalized with wild‐type NOTCH3 in the endoplasmic reticulum, whereas the majority of GRP78/BiP was translocated into the nuclei of cells expressing mutant NOTCH3. Cell proliferation and viability were higher for cells expressing mutant NOTCH3 than for those expressing wild‐type NOTCH3. We identified novel NOTCH3 mutations in PAH patients and revealed that these mutations were involved in cell proliferation and viability. NOTCH3 mutants induced an impairment in NOTCH3‐HES5 signaling. The results may contribute to the elucidation of PAH pathogenesis.